Bottom Passing Skills In Learning Mini Volleyball In Students Of Sdn Kedungbanteng 02 Bakung - Mufadilla, Rana Wildania; Ernata, Yusvidha; Kusmawati, Wiwik (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This research aims to determine the ability of underpassing skills in learning mini volleyball among students at SDN Kedungbanteng 02 Bakung. The subjects of this research were 19 class V students of SDN Kedungbanteng 02 Bakung. This research is quantitative descriptive research, the research method is a survey method with data collection techniques using tests and measurements. The data obtained were in the form of test results and measurements of bottom passing skills in learning mini volleyball for students at SDN Kedungbanteng 02 Bakung. It can be concluded that the bottom passing skills in learning mini volleyball among students at SDN Kedungbanteng 02 Bakung fall into the very good category as many as 2 students or 10%, the good category as many as 4 students or 21%, the fair category as many as 7 students or 37% and in the less than category there were 6 students or 32%.